Quaternary and Quintenary Semicontinuous Distillation - Wijesekera, Kushlani (My University, 2015)
The separation of four or more components traditionally requires the use of three or more distillation columns. Due to the associated high costs, process intensification techniques have been studied. Semicontinuous separation is one method that allows multiple separations using one column integrated with middle vessels. This thesis aims to develop a new semicontinuous separation process that can separate a mixture with four or more components into high purity products with one column and two or more middle vessels. It is an extension of the conventional ternary semicontinuous process, which has been repeatedly shown to be profitable at intermediate throughputs when compared to continuous systems. The semicontinuous process operates in a forced cycle, with three operating modes that ensure separation objectives are met. The performance of the proposed quaternary semicontinuous separation is analyzed through rigorous dynamic simulations over a range of production capacities. To determine the feasibility, operability, and applicability to non-ideal mixtures, three case studies were considered: 1. Equimolar mixture of alkanes (n-hexane; n-heptane; n-octane; n-nonane). 2. Equimolar mixture of aromatics (benzene; toluene; ethyl-benzene; and o-xylene). 3. Non-ideal mixture of mixed-alcohols (methanol, ethanol, and water; propanol; isobutanol; pentanol and hexanol) The extendibility of the quaternary semicontinuous separation process, referred to as quintenary semicontinuous separation, is then evaluated on a five-component alkane mixture (n-hexane; n-heptane; n-octane; n-nonane; n-decane), via three case studies: 1. Equimolar mixture 2. Non-equimolar mixture, rich in light and heavy components. 3. Non-equimolar mixture, rich in intermediate components. The results for both the quaternary and quintenary semicontinuous processes indicate that this new technique is successful at achieving separation objectives while staying within safe operating limits. Comparison of both equimolar mixtures of alkanes for quaternary and quintenary semicontinuous processes with continuous systems indicates that the proposed system is profitable for intermediate flow rates.
Keywords: Semicontinuous distillation; Process design; Alkanes; BTEX; Butanol; Process control; Quaternary; Quintenary